Reef lobsters of the genus Enoplometopus A. Milne-Edwards, 1862 (Crustacea: Decapoda: Nephropidea) from the KUMEJIMA 2009 Expedition in Okinawa, with the second record of the rare species E. chacei Kensley & Child, 1986 - Chan, Tin-Yam; Fujita, Yoshihisa (Zootaxa, 2012)
Two reef lobsters of the genus Enoplometopus A. Milne-Edwards, 1862, were collected during the KUMEJIMA 2009 Ex-pedition. The first is the very rare species Enoplometopus chacei Kensley & Child, 1986, which was previously knownonly from the male holotype collected in the Philippines. It is found that E. chacei has two colour forms: one form withthe body covered with red dots while the other form completely lacking red dots on the body. The second species collectedis E. voigtmanni Türkay, 1989, and represents the first recorded male of this species. Colour photographs are provided for the two species. The characters distinguishing E. chacei and E. voigtmanni from their closest congeners are discussed.